Perceived Meanings by Women and Men in “Identical Twins and Best Friends” Olay Advertisement - Fransisca Theresia Kurniawan (Institute of Research and Community Outreach - Petra Christian University, 2017)
This study observes the perceived meanings produced by women and men as respondents from different gender group can produce different perceived meanings. Using process of signification, the study of myth and decoding, the writer analyzed how meanings are perceived in Olay “Identical Twins And Best Friends” video commercial. The study uses descriptive qualitative approach. The finding is that in perceiving, women respondents are more likely to relate the women in the video with themselves about beauty, their own experience, and relationship with their sisters; while men respondents are most likely to relate them with their ideal type of women, older people and other female friends. Through this study, the writer expects that the result will help the readers understand the influence of gender in perceiving meanings from an advertisement.